Soil carbon dynamics are linked to tree species growth strategy in a naturally regenerating tropical forest - Wallwork, Abby; Castro-Trujillo, Biancolino; Banin, Lindsay F.; Dent, Daisy H.; Skiba, Ute; Kerdraon, Deirdre; Sayer, Emma J. (Frontiers in Forests and Global Change, 2023)
Secondary tropical forests are increasingly important for their role in the global carbon (C) balance as they can rapidly accumulate aboveground biomass C during regrowth. Substantial amounts of plantderived carbon are also incorporated into the soil through decomposition processes, but our understanding of soil C dynamics during forest regrowth is limited. Secondary succession is characterized by a shift in tree functional groups from light-demanding to shade-tolerant species over time, which can influence rates of C turnover via differences in litter quality and by modifying the decomposition environment. Changes in decomposition processes in turn affect the amount of organic C stored in the soil or released to the atmosphere as CO2. Consequently, understanding how tree functional composition influences C turnover during decomposition could help us predict soil C storage during tropical forest regrowth.We experimentally explored the relationship between tree functional groups and soil C dynamics (decomposition and respiration) by conducting a litter decomposition experiment across a successional gradient of naturally regenerating tropical forest. We created litter mixtures representing tree communities differing in their shade tolerance, as well as a functionally diverse litter mixture, and observed litter mass loss and soil respiration as measures of C turnover over a six month period. Litter from light-demanding species decomposed faster than litter from shade-tolerant species, which was reflected in the pattern of soil respiration. There were no clear patterns of increasing or decreasing rates of litter decay or soil respiration with increasing forest age, but there was an interaction between stand age and litter type which influenced both decomposition and soil respiration rates. Interestingly, soil respiration from the functionally diverse litter mixture was significantly higher in the younger than Running Title 2 older forest stands, and the functionally diverse litter mixture decayed more rapidly than expected in one of the younger stands. Our findings highlight the potential importance of functionally diverse plant inputs, as well as the interaction between local environmental attributes and litter type, for soil C dynamics in tropical forests.